Sports Bra Design Based on Dynamic Elder Women Avatar (Journal of Fiber Bioengineering and Informatics, 2023)
Elder women often suffer from chest pain and pressure discomfort due to breast displacement duringexercise. To design functional sports bras that will mitigate chest pain and pressure discomfort underdynamic conditions, a survey was completed to find out the bra design special requirements and simulationexperiments were carried out to investigate breast displacement rules. A standard sized running womanwas selected as a subject to determine the typical breast movement positions, and an elder womanavatar was used to simulate the breast displacement. The results showed that by dividing the bra intodifferent functional areas, the breast movement postures can be generated on the virtual model andthis method could be applied to develop ergonomic sports bras that can limit the breast movement forelder females. Approaches involved in this research are also suitable to design sportswear with specificfunctional requirements for various age women.
Keywords: Sports bra; Breast displacement; Elder women; Avatar; Pattern; Apparel design